Motion correction software in Myocardial Perfusion Imaging: is it useful? - Cunha, L. (2009)
Myocardial Perfusion Imaging (MPI) is a very important tool in the assessment of Coronary Artery Disease (CAD) patients and worldwide data demonstrate an increasingly wider use and clinical acceptance. Nevertheless, it is a complex process and it is quite vulnerable concerning the amount and type of possible artefacts, some of them affecting seriously the overall quality and the clinical utility of the obtained data.